Relationship between social support and depressive symptoms among internal migrant workers and the mediating role of healthy lifestyle: a cross-sectional study in China - Yunyun Wang; Beizhu Ye; Clifford Silver Tarimo; Yiyang Chen; Mingze Ma; Jingru Liu; Shuo Han; Kunyu Xue; Binghe Zuo; Yalin Song (BMJ Open)
Objectives To investigate the association between social support and depressive symptoms among internal migrant workers with a focus on the mediating role of a healthy lifestyle.Design Cross-sectional study.Setting The research was conducted among internal migrant workers in Henan Province, China, in August 2023.Participants Internal migrant workers are defined as individuals residing outside their registered household location (excluding mobility within the municipal district) and participating in various social and economic activities, including employment, entrepreneurship and social services.Primary outcome measures and analyses Social support was measured using the Chinese version of the social support rating scale. The severity of depression among the study participants was evaluated using the Patient Health Questionnaire-9. A healthy lifestyle was assessed based on the questionnaire we developed based on the American Medical Association Healthy Lifestyle Scale. Statistical analyses, including logistic regression, Spearman’s correlation and mediation analysis, were deployed to explore the associations between social support, healthy lifestyle and depressive symptoms.Results Among 19 326 participants, 21.45% exhibited depressive symptoms, with a higher prevalence observed among males. Social support levels among internal migrant workers were found to be lower than those in the general population, and higher social support was significantly associated with a decreased risk of depressive symptoms (OR=0.102, 95% CI: 0.086 to 0.121). Mediation analysis revealed that a healthy lifestyle partially mediated the relationship between social support and depressive symptoms among internal migrant workers, with a mediation effect of −0.063, accounting for 18.75% of the total effect.Conclusion This study provides insights into the complex interplay between social support, healthy lifestyle and depressive symptoms among internal migrant workers in China. Implementing interventions aimed at enhancing social support and promoting healthy lifestyle behaviours can significantly improve the mental health and overall well-being of internal migrant workers.